Effectiveness of exercise interventions in the prevention of excessive gestational weight gain and postpartum weight retention: a systematic review and meta-analysis. Issue 21 (18th October 2018) - Ruchat, Stephanie-May; Mottola, Michelle F; Skow, Rachel J; Nagpal, Taniya S; Meah, Victoria L; James, Marina; Riske, Laurel; Sobierajski, Frances; Kathol, Amariah J; Marchand, Andree-Anne; Nuspl, Megan; Weeks, Ashley; et al.
Abstract : Objective: Gestational weight gain (GWG) has been identified as a critical modifier of maternal and fetal health. This systematic review and meta-analysis aimed to examine the relationship between prenatal exercise, GWG and postpartum weight retention (PPWR). Design: Systematic review with random effects meta-analysis and meta-regression. Online databases were searched up to 6 January 2017. Study eligibility criteria: Studies of all designs in English, Spanish or French were eligible (except case studies and reviews) if they contained information on the population (pregnant women without contraindication to exercise), intervention (frequency, intensity, duration, volume or type of exercise, alone ["exercise-only"] or in combination with other intervention components [eg, dietary; "exercise + co-intervention"]), comparator (no exercise or different frequency, intensity, duration, volume or type of exercise) and outcomes (GWG, excessive GWG (EGWG), inadequate GWG (IGWG) or PPWR). Results: Eighty-four unique studies (n=21 530) were included. 'Low' to 'moderate' quality evidence from randomised controlled trials (RCTs) showed that exercise-only interventions decreased total GWG (n=5819; −0.9 kg, 95% CI −1.23 to –0.57 kg, I 2 =52%) and PPWR (n=420; −0.92 kg, 95% CI −1.84 to 0.00 kg, I 2 =0%) and reduced the odds of EGWG (n=3519; OR 0.68, 95% CI 0.57 to 0.80, I 2 =12%) compared with no exercise. 'High' quality evidence indicated higher odds of IGWG with prenatal exercise-only (n=1628; OR 1.32, 95% CI 1.04 to 1.67, I 2 =0%) compared with no exercise. Conclusions: Prenatal exercise reduced the odds of EGWG and PPWR but increased the risk of IGWG. However, the latter result should be interpreted with caution because it was based on a limited number of studies (five RCTs).